Effect of Different Papain Concentrations on Yield and Quality of Tuna Eye Oil - Trilaksani, Wini; Nurhayati, Tati; Santoso, Joko; Riyanto, Bambang; Fauziah, Silva; Sinulingga, Fahri (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Highlight Research Innovative Use of By-Products: The study explores the use of tuna eye by-products, a rich source of docosahexaenoic acid (DHA), to reduce reliance on imported fish oil and promote sustainable utilization of fishery waste. Enhanced Extraction Methodology: Enzymatic extraction using papain at optimal concentrations significantly improves the yield and quality of tuna eye oil, achieving up to six times higher yield compared to other methods. Nutritional and Quality Benefits: The extracted oil demonstrated low Index of Atherogenicity (IA) and Index of Thrombogenicity (IT), indicating its potential as a heart-healthy dietary supplement, with DHA and EPA concentrations well preserved. Environmental and Safety Advantages: The enzymatic process is solvent-free, minimizing environmental impact and ensuring consumer safety, while also addressing challenges posed by extended sample storage during the COVID-19 pandemic. Abstract Docosahexaenoic acid (DHA), a crucial omega-3 fatty acid, plays a vital role in neurodevelopment and cardiovascular health. Indonesia relies heavily on imported fish oil, despite its significant potential in underutilized by-products like tuna eyes. This study investigates the optimization of papain enzyme concentration for enzymatic extraction of DHA-rich oil from tuna eyes, aiming to enhance yield and maintain quality. Using 1% papain at 55°C for 1 hour, the optimized process achieved an oil yield of 8.59 ± 0.69%, six times higher than cold extraction without enzymes. The extracted oil exhibited high oxidative stability with low Index of Atherogenicity (IA: 0.38–0.40) and Index of Thrombogenicity (IT: 0.20–0.21), while DHA content remained well-preserved at 27.82%. This method also demonstrated the capability to maintain oil quality even after prolonged storage during the COVID-19 pandemic. Compared to conventional methods, enzymatic extraction provides a sustainable and efficient alternative by reducing chemical solvent use, minimizing environmental impact, and maximizing the utilization of fishery by-products. These findings offer a scalable solution for producing high-value omega-3 oils, contributing to global dietary needs and promoting sustainability in the fishery industry.